International trade and inclusive development : building synergies (UN SantiagoCL, 2014)
Examines the contribution international trade can make to the renewed approach to development proposed in two key documents by ECLAC: Time for equality (2010) and Structural change for equality (2012). Seeks in particular, to evaluate how international trade impinges on growth and equality in the region.
Keywords: INTERNATIONAL TRADE